Gwent English: A comparative investigation of lexical items. - Benjamin A. Jones (Tradition Today, 2016)
Due to Gwent’s position on the border between Wales and England, the historicregion shares a hybrid identity of both Welshness and Englishness. During theage of traditional dialectology (i.e. nineteenth century until the mid-twentiethcentury), Gwent’s Anglo-Welsh dialect was investigated twice, first by the SED(Survey of English Dialects, circa 1951-1960) and then the SAWD (Survey ofAnglo-Welsh dialects, circa 1971) – a testament to its ambiguous cultural/political identity. These studies provided substantial lexical information on theregion. A decade ago, collections of dialectal material by BBC Voices, an internetproject conducted between 2004 and 2005, provided not only new frameworks fordialect surveying (internet-based), but also additional material for Gwent English.This paper summarises some of the findings of a further internet-based dialectsurvey constructed in 2013 that elicited the speech of 44 young people in Gwentand assessed their regional lexis and their linguistic identity. The material wasthen compared with the historic dialect records to determine whether there hadbeen changes in Gwent English between the 1970s and 2013. Results indicatedthat the region still contained lexis obtained by the SAWD and Voices, but newlexis was also recorded, some of which was of Welsh origin, whilst other sourcesstemmed from American English and internet slang. Their linguistic identity/perception was also, understandably, complex.